2018
DOI: 10.7196/samj.2018.v108i11.12979
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of self-induced late pregnancy termination in women presenting to a tertiary hospital in the Eastern Cape Province, South Africa

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Thirty-nine studies described using misoprostol alone for abortion self-management. Six studies provided specifics of misoprostol only regimens (50,68,(85)(86)(87)(88). One study of misoprostol use among women along the Thailand/Burma border describes community health workers dispensing 12 misoprostol tablets (200mcg each), and instructing the woman to "vaginally take 800mcg followed 24 h later with another 800mcg dose and a third 800mcg dose one week after the initial administration, if needed," in accordance with evidence-based guidelines at that time (86).…”
Section: Misoprostol Onlymentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty-nine studies described using misoprostol alone for abortion self-management. Six studies provided specifics of misoprostol only regimens (50,68,(85)(86)(87)(88). One study of misoprostol use among women along the Thailand/Burma border describes community health workers dispensing 12 misoprostol tablets (200mcg each), and instructing the woman to "vaginally take 800mcg followed 24 h later with another 800mcg dose and a third 800mcg dose one week after the initial administration, if needed," in accordance with evidence-based guidelines at that time (86).…”
Section: Misoprostol Onlymentioning
confidence: 99%
“…A study in Uruguay reported a majority of participants administering one 800mcg dose of misoprostol vaginally (85). Another study reported details on misoprostol dosage among participants with pregnancies at or beyond 24 weeks gestation, which ranged from 400 to 1,200mcg almost all taken orally (88). Another two studies reported more generally on regimen, describing use of between one and eight misoprostol tablets, administered either vaginally or orally(87); and another described participants taking "four misoprostol pills, two or three vaginally and one or two orally"( 50).…”
Section: Misoprostol Onlymentioning
confidence: 99%
See 3 more Smart Citations